The Ultimate Trainers - Shipton, Paul (Oxford Oxford University Press, 2014)
In The Ultimate Trainers Jake finds a pair of gleaming new trainers in the rubbish. He soon finds that there is more to them than meets the eye... TreeTops Fiction contains engaging novels from top authors and illustrators with the variety children need to develop a love of reading!
Include Illustrations
Keywords: Running shoes -- Time travel -- Cross-country running